PENGARUH KUALITAS LAYANAN DAN FASILITAS TERHADAP KEPUASAN KONSUMEN TAMAN WISATA CANDI BOROBUDUR, JAWA TENGAH - arifin arifin; Rahmawati Riantisari; Sugiyono Sugiyono (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2020)
The purpose of this study was to analyze consumer satisfaction Borobudur Central Java Temple Tourism Park. This study uses service and facility quality variables to analyze customer satisfaction at Borobudur Tourism Park. The sampling technique used by multiplying 5 times the number of question items, then the sample results obtained by 155 people. The result was that 150 questionnaires were answered by visitors to Borobudur Temple Tourism Park while 5 questionnaires were not filled out by visitors so they were not included in the data analysis. Then the response rate in this study was 96.77%. The analytical tool used to test the research instrument uses the validity and reliability test while to test the hypothesis is the Multiple Linear Regression Analysis, t Test and F. The result is that Service Quality has a significant effect on Consumer Satisfaction of Borobudur Temple Tourist Park Consumers, Facilities do not significantly influence Satisfaction Consumers Borobudur Temple Tourism Park Consumers and Quality of Service and Facilities simultaneously affect Consumer Satisfaction Borobudur Temple Tourism Park Consumers Keywords: Service quality, Facilities and customer satisfaction, Borobudur Temple